Effectiveness of a WHO self‐help psychological intervention for preventing mental disorders among Syrian refugees in Turkey: a randomized controlled trial. Issue 1 (11th January 2022) - Acarturk, Ceren; Uygun, Ersin; Ilkkursun, Zeynep; Carswell, Kenneth; Tedeschi, Federico; Batu, Mine; Eskici, Sevde; Kurt, Gulsah; Anttila, Minna; Au, Teresa; Baumgartner, Josef; Churchill, Rachel; et al.
Abstract : Refugees are at high risk of developing mental disorders. There is no evidence from randomized controlled trials (RCTs) that psychological interventions can prevent the onset of mental disorders in this group. We assessed the effectiveness of a self‐help psychological intervention developed by the World Health Organization, called Self‐Help Plus, in preventing the development of mental disorders among Syrian refugees experiencing psychological distress in Turkey. A two‐arm, assessor‐masked RCT was conducted in two Turkish areas. Eligible participants were adult Syrian refugees experiencing psychological distress (General Health Questionnaire ≥3), but without a diagnosis of mental disorder. They were randomly assigned either to the Self‐Help Plus arm (consisting of Self‐Help Plus combined with Enhanced Care as Usual, ECAU) or to ECAU only in a 1:1 ratio. Self‐Help Plus was delivered in a group format by two facilitators over five sessions. The primary outcome measure was the presence of any mental disorder assessed by the Mini International Neuropsychiatric Interview at six‐month follow‐up. Secondary outcome measures were the presence of mental disorders at post‐intervention, and psychological distress, symptoms of post‐traumatic stress disorder and depression, personally identified psychological outcomes, functional impairment, subjective well‐being, and quality of life at post‐intervention and six‐month follow‐up. Between October 1, 2018 and November 30, 2019, 1, 186 refugees were assessed for inclusion. Five hundred forty‐four people were ineligible, and 642 participants were enrolled and randomly assigned to either Self‐Help Plus (N=322) or ECAU (N=320). Self‐Help Plus participants were significantly less likely to have any mental disorders at six‐month follow‐up compared to the ECAU group (21.69% vs. 40.73%; Cramer's V = 0.205, p<0.001, risk ratio: 0.533, 95% CI: 0.408‐0.696). Analysis of secondary outcomes suggested that Self‐Help Plus was not effective immediately post‐intervention, but was associated with beneficial effects at six‐month follow‐up in terms of symptoms of depression, personally identified psychological outcomes, and quality of life. This is the first prevention RCT ever conducted among refugees experiencing psychological distress but without a mental disorder. Self‐Help Plus was found to be an effective strategy for preventing the onset of mental disorders. Based on these findings, this low‐intensity self‐help psychological intervention could be scaled up as a public health strategy to prevent mental disorders in refugee populations exposed to ongoing adversities.